Final judgments : duty and emotion in Roman wills, 200 B.C.-A.D. 250 - Champlin, Edward, 1948- (University of California Press, 1991)
Freed from the familial and social obligations incumbent on the living, the Roman testator could craft his will to be a literal ""last judgment"" on family, friends, and society. The Romans were fascinated by the contents of wills, believing the will to be a mirror of the testator's true character and opinions. The wills offer us a unique view of the individual Roman testator's world. Just as classicists, ancient historians, and legal historians will find a mi.